(untitled) (IAHS Medical Journal, 2022)
Background: An antimicrobial is an agent, that kills micro organisims or prevents their growth. The purpose of this study is to evaluate antimicrobial prescribing behaviors in the Dermatology Outpatient Department. Materials and methods: This multi-centered, cross-sectional study was conducted at Dermatology Outpatient Department of three tertiary care hospitals in Chattogram division, Bangladesh during the period October, 2021 to April, 2022. Results: During the study period, 463 prescriptions were obtained. Over half of the participants were female (57%) and between the ages of 21 to 40 years. The majority of patients were diagnosed with eczema (19%), acne (17%) and scabies (15%). Most commonly prescribed antimicrobials was Azithromycin (22%) followed by Permethrin (16%) and Erythromycin (7%). In most cases, antimicrobials were recommended for more than two weeks (60%). Nearly half of the antimicrobials (53 %) were recommended as combination of systemic and topical route. Conclusion: Current study found that dermatologists frequently recommended broad-spectrum antimicrobials for extended periods of time, which may lead to antimicrobial resistance. There is a need for continuing medical education on the appropriate use of antimicrobials, which will result in the effective management of skin diseases. IAHS Medical Journal Vol 5(1), June 2022; 16-21